Review of therapy and therapeutic problems in patients with asthma in primary health care - Lazarević, Katarina; Kovačević, Milena; Ćulafić, Milica; Jovanović, Marija; Roganović, Maša; Vezmar Kovačević, Sandra; Vučićević, Katarina; Miljković, Branislava (Archives of Pharmacy, 2022)
Asthma represents a serious global burden because, despite available therapy, poor health and socio-economic outcomes are reported. The aim of this paper is to analyse treatment in patients with asthma and to identify drug-related problems. An observational study included 57 adult asthma patients of both genders. Data were collected in community pharmacies during 2016, by filling out questionnaires. Descriptive analysis was performed in Microsoft® Office Excel 2010. Respondents’ average age was 49.7±17.4, 38.6% were men. Patients used short-acting (36.8%) and long-acting beta-2 agonists (8.8%), inhaled corticosteroids (28.1%) and combined preparations (73.7%). More than 50% of patients used inhaled anticholinergics, while theophylline was used in 31.6%, which is in discordance with the asthma guidelines, due to poor efficacy and safety profile. Also, this may indicate that patients do not accept inhalation therapy because of demanding technique or higher cost. Allergic rhinitis, obesity, hypertension, and gastroesophageal reflux disease were the most common comorbidities. Potentially inadequate co-therapy included beta-blockers (21.1%), angiotensin-converting enzyme inhibitors (28.1%), aspirin/nonsteroidal antiinflamatory drugs (21.1% and 29.8%), which may worsen asthma. It is discouraging that 26.3% of patients were smokers, 35.1% did not know the triggers for asthma, and only 1 patient used the asthma action plan. The results show a higher prevalence of therapy appropriate for severe asthma stages, which implies poor disease control and poor outcomes. There is a need for the implementation of pharmaceutical care services and better education of patients with asthma.